The Role of Immigration in the Population Dynamics of European Union Member States - Cabańska , Judyta (Studia Oeconomica Posnaniensia, 2013)
The population stock is influenced by a combination of natural change (the difference between live births and deaths) and net migration. In the light of the on-going trend of population ageing experienced in the EU, international migration plays a significant role in the size and structure of the population in most EU countries. The relative economic prosperity and political stability of the EU are thought to have exerted a considerable pull effect on immigrants. The aim of this paper is to discuss the impact of immigration on the population stock in EU member states. Additionally, the article presents the proportion of foreigners in the EU-27 population.